2017
DOI: 10.1111/avj.12621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insemination site and diameter of the pre‐ovulatory follicle on the odds of pregnancy in heifers using sexed or non‐sexed semen

Abstract: Insemination site did not affect pregnancy per AI, but heifers with an 18-22 mm pre-ovulatory follicle at insemination had better odds of pregnancy for both sexed and non-sexed inseminations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A University of Sydney study discusses the merits of using sexed semen in the dairy cattle industry. 5 Sexed semen (i.e. semen that has gone through flow cytometry to separate out the sperm containing the y chromosome) consistently results in approximately 90% of heifer calves.…”
Section: Production Animalsmentioning
confidence: 99%
“…A University of Sydney study discusses the merits of using sexed semen in the dairy cattle industry. 5 Sexed semen (i.e. semen that has gone through flow cytometry to separate out the sperm containing the y chromosome) consistently results in approximately 90% of heifer calves.…”
Section: Production Animalsmentioning
confidence: 99%
“…Recently significant progress has been made in the area of spermatozoa sex pre‐selection through flow cytometer (De Graaf et al, 2007). The sperm sorting sex pre‐selection through flow cytometer is 85%–95% accurate method in livestock production (Ingenhoff et al, 2017; Maxwell et al, 2004). This advancement has led to the commercialization of bovine sex‐sorting technology around the world.…”
Section: Introductionmentioning
confidence: 99%
“…
Recently significant progress has been made in the area of spermatozoa sex pre-selection through flow cytometer (De Graaf et al, 2007). The sperm sorting sex pre-selection through flow cytometer is 85%-95% accurate method in livestock production (Ingenhoff et al, 2017;Maxwell et al, 2004). This advancement has led to the commercialization of bovine sex-sorting technology around the world.However, the flow cytometry procedure is costly and it can also reduce the lifetime of sex-sorted sperm (Maxwell et al, 2004).Many experiments indicated that in comparison to sperm typically utilized for artificial insemination in cattle, the quality of sex-sorted sperm was substantially lower (Seidel Jr et al, 1999).
…”
mentioning
confidence: 99%